The Implementation of Mobile-Based Learning on Vocational High School Students: Systematic Literature Review - Handoyo, Febri; Tuwoso, Tuwoso; Budi, Setiyo (Jurnal Edukasi Elektro, 2025)
This study aims to analyze the impact of mobile-based learning, especially android-based, on learning outcomes, student interest, and work readiness in Vocational High School. Using the Systematic Literature Review (SLR) method based on the PRISMA approach, researchers identified and analyzed 31 relevant publications from 2020 to 2024. The results of this study indicate that android-based learning significantly improves learning outcomes of vocational high school students, especially in vocational subjects. Android-based applications provide flexibility and interactivity that allow students to understand the subject matter more deeply than conventional learning methods. In addition, android-based application also plays an important role in increasing student interest. Interactive features, such as interesting simulations and visualizations, have been shown to increase student interest in the learning process, making learning more interesting and relevant to them. On the other hand, the use of android media in learning also shows a positive impact on student work readiness. Project Based Learning (PjBL) and practical simulations integrated into android-based learning applications strengthen students' basic knowledge and help them to develop practical skills that are relevant to the demands of the industrial world. Overall, this study confirms that android-based learning has great potential in improving the quality of Vocational High School education, both in terms of academic aspects and work readiness skills.